Informed consent in orthopaedics: do patients in the United Kingdom understand the written information we provide?. (September 2018) - Seewoonarain, S.; Johnson, A. A.; Barrett, M.
Abstract : Aims: Informed patient consent is a legal prerequisite endorsed by multiple regulatory institutions including the Royal College of Surgeons and the General Medical Council. It is also recommended that the provision of written information is available and may take the form of a Patient Information Leaflet (PIL) with multiple PILs available from leading orthopaedic institutions. PILs may empower the patient, improve compliance, and improve the patient experience. The national reading age in the United Kingdom is less than 12 years and therefore PILs should be written at a readability level not exceeding 12 years old. We aim to assess the readability of PILs currently provided by United Kingdom orthopaedic institutions. Patients and Methods: The readability of PILs on 58 common conditions provided by seven leading orthopaedic associations in January 2017, including the British Orthopaedic Association, British Hip Society, and the British Association of Spinal Surgeons, was assessed. All text in each PIL was analyzed using readability scores including the Flesch–Kincaid Grade Level (FKGL) and the Simple Measure of Gobbledygook (SMOG) test. Results: The mean FKGL was 10.4 (6.7 to 17.0), indicating a mean reading age of 15 years. The mean SMOG score was 12.8 (9.7 to 17.9) indicating a mean reading age of 17 years. Conclusion: Orthopaedic-related PILs do not comply with the recommended reading age, with some requiring graduate-level reading ability. Patients do not have access to appropriate orthopaedic-related PILs. Current publicly available PILs require further review to promote patient education and informed consent. Cite this article: Bone Joint J 2018;100-B:1253–9.